Isolasi Dan Karakterisasi Senyawa Steroid Dari Ekstrak Biji Mahoni (Swietenia mahagoni Jacq.) - Fadillah Maryam; Subehan Subehan; Lilis Musthainah (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
Mahogany seeds (Swietenia mahagoni Jacq.) Have many benefits as drugs such as febrifuge, diabetes (Diabetes Mellitus), high blood pressure, fat decay, colds, colitis, diarrhea, wounds, and ulcers. Swietenia mahagoni Jacq Contain steroid compounds. This study aims to determine the characterization of steroid compounds isolated from mahogany seed extract (Swietenia mahagoni Jacq.). Extracts were obtained from maceration processes using n-hexane, ethyl acetate, and ethanol 70% solvents with percent of rendament of 6.34%, 7.34%, and 8% respectively. The test results for the chemical content of ethyl acetate extract positively contained steroids. 5 grams of extract was carried out using conventional column chromatography to produce 6 fractions. Fraction 6 were selected and continued with preparative thin layer chromotography and produced 2 isolates. Isolates P2b which showed one tonggal stain on the TLC profile with a value of Rf 0.50 were continued to be analyzed by UV-Vis and FT-IR spectrophotometry.The results of UV-Vis spectrophotometric isolates P2b had maximal absorption at a wavelength of 253.50 nm. FT-IR data shows the presence of functional groups C-H, C-O, C = O, C = C, and O-H whichare thought to be steroid compounds.